2012
DOI: 10.1590/s0100-69162012000600007
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a diesel engine fueled with a preheated blend of soybean oil and petrodiesel

Abstract: Brazil is doing a major effort to find alternatives to diesel oil as combustible. Some study lines are oriented to the development of vegetable oils used as fuel, as a source of getting cheaper and have higher energy density than the converted vegetable oils, and less risk of environmental contamination. The aim of this study was to evaluate the performance, the useful life of the lubricant and some components of a Diesel Cycle engine, with an electronic injection system, in a long-term test operating with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
4
0
2
Order By: Relevance
“…The results were similar to those found by DELALIBERA et al (2010) for sunflower oil with and without preheating (90 °C). For the consumption results under load regime, corroborate with those presented by MARTINI et al (2012), which observed a tendency on increase of the consumption with the increase of temperature on preheating of soybean oil in engine under regime of absorption at 70% of the nominal power.…”
Section: Fuel Consumptionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results were similar to those found by DELALIBERA et al (2010) for sunflower oil with and without preheating (90 °C). For the consumption results under load regime, corroborate with those presented by MARTINI et al (2012), which observed a tendency on increase of the consumption with the increase of temperature on preheating of soybean oil in engine under regime of absorption at 70% of the nominal power.…”
Section: Fuel Consumptionsupporting
confidence: 89%
“…In spite of being favorable from the energetic and environmental point of view, the direct use of vegetable oils in diesel engines is problematic. Studies with several oils have shown that the application of these as fuel causes carbonization excess of the combustion chamber; contaminates and degrades the lubricant and causes accelerated wear of moving parts (HAZAR & AYDIN, 2010;DELALIBERA et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…According to MELILLO et al (2009) there is a global incentive for the partial substitution of diesel fuel of mineral origin by others from plant and animal origin, commonly called biodiesel. Added to this, the growing concern over environmental pollution and the increase in oil prices has driven the development of research in seeking for renewable fuels (DELALIBERA, 2012).…”
Section: Introductionmentioning
confidence: 99%
“… Problems related to high concentration of biodiesel: o Diesel fuel with high concentration of biodiesel can reduce engine life. Delalibera, Campolina, Neto, and Ralisch (2012) when analyzing the performance of diesel engine fuel with a preheated blend of high concentration of biodiesel had identified that engine fuel injectors had reduced life, common rail system was unstable in delivering fuel, and there an increase of particulate mater (PM). o The type of engine oil sold in Latin America could impact engine durability.…”
Section: Literature Reviewmentioning
confidence: 99%